EVALUATION OF THE EFFICACY OF ALENDRONIC ACID IN DENTAL IMPLANTATION (literature review) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Normal functioning of bone tissue is ensured by a balance between the interrelated processes of bone resorption and bone formation, neogenesis. Bone remodelling depends on the balanced work of osteoclasts and osteoblasts, adequate mineralisation, and is controlled by many factors, both at the systemic level and locally, such as hormones, cytokines, and growth factors. Disturbance of bone tissue metabolism, predominance of the resorption process leads to the formation of osteopenia and osteoporosis, which is accompanied by the loss of support, protective and depositing functions of bone tissue